Measuring transportation network performance - National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program; American Association of State Highway and Transportation Officials; United States. Federal Highway Administration; Cambridge Systematics; University of Maryland (College Park, Md.). Center for Advanced Transportation Technology; Resource Systems Group, Inc. (Washington, D.C. : Transportation Research Board, 2010)
This guidebook provides methods for integrating performance measures from individual transportation modes and multiple jurisdictions and for developing new measures, if needed, to monitor transportation network performance. These network performance measures can be used to improve system management, planning, and investment decisions and can be applied to various scenarios. The guidebook should be of immediate use to practitioners in state, regional, or local governments; specially designated authorities; or those in the private sector who are responsible for measuring, operating, and investing in the performance of multimodal and/or multijurisdictional transportation networks.
Ch. 2. Understanding Network Performance Measurement -- Ch. 3. Regional Scenario - Defining Community Goals Across Jurisdictions -- Ch. 4. Regional Scenario - Multimodal and Multistrategy Investment Prioritization -- Ch. 5. Peer-to-Peer Scenario - Multistate Partnership for System Operations -- Ch. 6. Peer-to-Peer Scenario - Megaregional Partnership to Address Growth -- Ch. 7. Intra-Agency Scenario - Linking Planning and Operations at a State DOT.
At head of title: National Cooperative Highway Research Program.
Includes bibliographical references (p. 75-76).
Also available online.
Research sponsored by the American Association of State Highway and Transportation Officials in cooperation with the Federal Highway Administration
Keywords: Transportation -- United States -- Planning; Transportation corridors -- United States -- Planning; Network analysis (Planning).; performance; evaluation and assessment; Transportation networks